Analisis Kinerja Keuangan Dan Kemampuan Keuangan Pemerintah Daerah Dalam Pelaksanaan Otonomi Daerah Di Kabupaten Barito Kuala Tahun 2015- 2018 - Sri Wardani; Muhammad Saleh (PPJP ULM, 2020)
This study aims to assess the financial performance of the local government ofBarito Kuala Regency by using the Financial Ratio Analysis of the Regional Budget andRevenue (APBD) of Barito Kuala Regency in the 2015-2018 Fiscal Year. In this study,the analysis tools used are Regional Financial Performance Analysis and Analysis ofRegional Financial Capabilities. Financial Performance Analysis is measured bycalculating the Independence Ratio, Activity Ratio, Effectiveness and Efficiency Ratio,and Growth Ratio. At the same time, Financial Ability Analysis is measured bycalculating the Routine Ability Index and Fiscal Autonomy Degree Ratio.Based on the results of the calculation of Regional Financial Performance, it canbe concluded that the relationship pattern of regional independence is instructive,meaning that the provincial government is still very dependent on central governmenttransfer funds. Simultaneously, the Activity Ratio level is not balanced, where localgovernments prioritize Indirect Expenditure compared to Direct Expenditure. However,the level of regional effectiveness and efficiency ratio shows a practical and efficientlevel. Based on the average growth ratio shows that growth is fluctuating from year toyear. Change tends to be positive, but Direct Spending shows negative growth. Whilebased on the results of the calculation of Regional Financial Capabilities, it can beconcluded that the results of the analysis of Routine Capacity Index and Fiscal AutonomyDegree Ratio are on a scaling scale, meaning that the financial capacity of Barito Kualadistrict is not yet ideal, because the role of the central government is still very dominant.